Electrical and thermal conductivity of ethylene vinyl acetate composite with graphene and carbon black filler. (December 2018) - Azizi, Sohrab; David, Eric; Fréchette, Michel F.; Nguyen-Tri, Phuong; Ouellet-Plamondon, Claudiane M.
Abstract: Ethylene vinyl acetate (EVA) composites, including two different carbonaceous conductive fillers, carbon black (CB) and commercially available graphene (G), were fabricated by solvent-casting and melt compounding methods. The effect of additives and process conditions on electrical and thermal properties of composites was investigated. The dielectric responses of EVA composites were characterized by a percolation threshold of 15 wt % for EVA/G prepared by solvent-casting. However, as the EVA/G15% was also subsequently extruded, the applied shear stress induced by extrusion caused deterioration of the electrical network and reduced the composite's electrical conductivity. A percolating network was found for the EVA composites containing CB at around 5–7 wt % with 10 orders of magnitude increase in electrical conductivity with respect to the neat EVA. The thermal conductivity of EVA/CB7% and EVA/G15% increased 16 and 22% respectively, in comparison to the neat EVA. Both additives increased the electrical and thermal conductivity of composites to be appropriate as jackets for high-voltage cables. Highlights: Electrical and thermal conductivity of EVA composites with two conductive additives were investigated. A percolation threshold was characterized by broadband spectroscopy for EVA/G at 15% filler content. EVA composites with CB filler was found to be conductive at 7 wt% CB filler content. Addition of graphene and carbon black enhanced the thermal conductivity and dynamic mechanical properties of the composite.